THE EFFECT OF WORD OF MOUTH ON THE DECISION TO USE WEDDING ORGANIZER ELEVEN SERVICES IN MAKASSAR CITY - Muhammad Arbi Alizar; Ikhwan Maulana Haeruddin, Zainal Ruma, Ichwan Musa, Ahmad Ali (International Journal Of Humanities, Social Sciences And Business (INJOSS), 2022)
This study aims to determine how the influence of Word of Mouth on the decision to use Wedding Organizer Eleven services in Makassar City. The independent variable in this study is Word Of Mouth while the dependent variable is Purchase Decision. The population in this study are WO Eleven users. While the sample used is as many as 65 respondents. The sampling technique in this study was carried out using a simple random sample method (Simple Random Sampling method). Data collection was done by using a questionnaire. The data analysis technique used is simple linear regression analysis using SPSS 25.00 for Windows. The results showed that the results showed that the Word of Mouth variable had a significant influence on the consumer purchasing decision variables of Wedding Organizer Eleven. The value of the regression coefficient of the Word of Mouth variable (b) is positive at 0.621, which means that for every additional one unit of Word of Mouth value, the value of the purchase decision will increase by 0.621. The regression coefficient is positive, so it can be said that the direction of the influence of the X variable on Y is positive.